ANALYSIS OF THE 7P MARKETING MIX STRATEGY TO ATTRACT CONSUMER INTEREST (CASE STUDY: PIZZA HUT DARMO SURABAYA) - Haninda, Rizka Novianty; Grandis, Dea Titania (Jurnal Baruna Horizon, 2025)
This research aims to analyze the implementation of the 7P marketing mix strategy (Product, Price, Place, Promotion, People, Process, and Physical Evidence) in attracting consumer interest at Pizza Hut Darmo Surabaya. The method used is descriptive qualitative with data collection techniques through observation, questionnaires, interviews, and documentation studies. The research findings indicate that the 7P marketing mix strategy plays a significant role in enhancing consumer attraction. The primary influencing factor is the consistent and innovative product quality (Product) along with friendly and professional service (People). The limitations of this research are focused on the 7P marketing mix strategy implemented by Pizza Hut Darmo Surabaya, without comparing it to other branches or competing restaurants. This research provides insights into the marketing elements that are most influential in attracting consumer interest, thus serving as a basis for strategic decision-making.